PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN TINGKAT HUTANG TERHADAP TAX AVOIDANCE - Desi Rahmawati; Dhiona Ayu Nani (Faculty of Economics and Business, 2021)
This study aims to analyze the effect of profitability, firm size, and debt level on tax avoidance. The sample in this study are mining companies listed on the Indonesia Stock Exchange during the 2016-2019 period. The sample in this study using purposive sampling method obtained a sample of 23 mining companies. Tests in this study using SPSS (Statistical Product and Service Solution) analysis tools and data analysis in this study using multiple linear regression analysis. The results of this study indicate that the profitability variable is negative on tax avoidance, company size has no effect on tax avoidance, while the level of debt has a negative and significant effect on tax avoidance. The variables of profitability, firm size, and debt level together have a significant effect on tax avoidance. Keywords: tax avoidance, profitability, firm size, debt level.